2014
DOI: 10.1089/cbr.2014.1649
|View full text |Cite
|
Sign up to set email alerts
|

Op18/Stathmin Is Involved in the Resistance of Taxol Among Different Epithelial Carcinoma Cell Lines

Abstract: NCI-H1299 cells are evidently resistant to taxol-induced cellular apoptosis, inhibition of cellular proliferation and wound recovery, as well as cell migration and invasion interference, which are closely associated with the changes of microtubule dynamics. High expression of Op18/stathmin is perhaps a crucial determinant of taxol-resistant development in NCI-H1299 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…In a previous study, we found that Epstein-Barr virusspecific protein-latent membrane protein 1 (LMP1) regulates the Op18/stathmin signaling pathway by mediating Cdc2, which accelerates cell cycle progression and promotes cell proliferation (16). In another recent study of ours, we confirmed that human NCI-H1299 non-small cell lung cancer cells highly expressing Op18/stathmin were the most highly resistant to taxol among 5 different cancer cells originating from epithelia, including CNE1, Hep3B-2, MGC, MCF-7 and NCI-H1299 (17).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In a previous study, we found that Epstein-Barr virusspecific protein-latent membrane protein 1 (LMP1) regulates the Op18/stathmin signaling pathway by mediating Cdc2, which accelerates cell cycle progression and promotes cell proliferation (16). In another recent study of ours, we confirmed that human NCI-H1299 non-small cell lung cancer cells highly expressing Op18/stathmin were the most highly resistant to taxol among 5 different cancer cells originating from epithelia, including CNE1, Hep3B-2, MGC, MCF-7 and NCI-H1299 (17).…”
Section: Introductionsupporting
confidence: 59%
“…Both the CNE1 cells and NCI-H1299 cells were a kind gift from Professor Ya Cao from the Cancer Research Institute of Central South University and cultured in RPMI-1640 (Gibco-BRL, Grand Island, NY, USA) with 10% fetal bovine serum (FBS; HyClone, Logan, UT, USA), 100 IU/ml penicillin and 100 µg/ml streptomycin at 37˚C, 5% CO 2 . CNE1 human cancer cells were testified to be the most sensitive to taxol among 5 various epithelial-deriving tumor cells in our previous study (17). Thus, they were used in this study for a comparison to the NCI-H1299 cells.…”
Section: Methodsmentioning
confidence: 99%
“…Chemoresistance to docetaxel with stathmin overexpression may be caused by the microtubule‐destabilizing activity of stathmin, which may diminish binding to docetaxel and increase binding to vincristine‐like drugs . Chemoresistance to cisplatin and 5‐fluorouracil with stathmin overexpression may be caused by the participation of stathmin overexpression in the cellular response to DNA damage and caspase‐6‐mediated cellular apoptosis, as described in previous studies conducted in head and neck cancer or colorectal cancer, respectively . To some extent, these reasons lead to the unsatisfactory clinical benefit of TPF induction chemotherapy in OSCC patients with high stathmin expression.…”
Section: Discussionmentioning
confidence: 93%
“…Our previous study suggested that stathmin acts as an oncogene and could be a potential antitumor therapeutic biomarker in OSCC . Several studies have shown that overexpression of stathmin influences the resistance of docetaxel and cisplatin . Based on the above findings, a new therapy regimen targeting stathmin looks promising and needs to be researched.…”
Section: Introductionmentioning
confidence: 97%
“…Although STMN1 over-expression has been reported to be positively correlated with lymph node metastasis and TNM staging [36, 37, 40], no association was proved in our study, which may be attributed to small sample size and different detection methods. Moreover, studies imply that cancer patients with low expression of STMN1 mRNA will have a favorable clinical efficacy after being treated with Taxol regimens [41, 42]. Silencing STMN1 enhances the sensitivity of gastric cancer cells to docetaxel, with the resistance index reducing to 3.41 [13].…”
Section: Discussionmentioning
confidence: 99%